Gynecomastia in adolescent males: current understanding of its etiology, pathophysiology, diagnosis, and treatment - Kotb Abbass Metwalley; Hekma Saad Farghaly (Korean Society of Pediatric Endocrinology, 2024)
Gynecomastia (GM) is a common and continuously evolving condition that commonly occurs during adolescence. It is the source of significant embarrassment and psychological stress in adolescent males. GM is characterized by enlargement of the male breast due to the proliferation of glandular ducts and stromal components. The main cause of GM during adolescence is physiological or pubertal GM, which is primarily attributed to an imbalance between estrogen and androgen activity. Physiological GM is typically transient and resolves within several months, although it may take several years to resolve. GM may also be caused by other pathological conditions and could be indicative of an endocrine disease. It is crucial to understand the pathogenesis of GM to distinguish it from normal developmental variants due to pathological causes. The aim of this review is to highlight the significance of GM during adolescence in terms of potential etiologies, clinical and laboratory diagnoses, and current management.